The Effect of Financial Literacy, Digital Payment, and Digital Accounting on the Financial Performance of MSMEs in Gebang District - Adyatma Kautsar; Irwan Sutirman Wahdiat (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to analyze the effect of financial literacy, digital payment, and digital accounting on the financial performance of MSMEs in Gebang District. This study uses a quantitative approach with primary data obtained through a questionnaire with a 1-5 Likert scale. The population in this study were MSMEs in Gebang District with a sample size of 122 MSME players. The analysis techniques used in this study were descriptive statistical analysis, validity test, normality test, multicollinearity test, heteroscedasticity test, multiple linear regression, T-test, F-test, and coefficient of determination using SPSS 27. The results showed that financial literacy and digital accounting had a positive and significant effect on financial performance, with digital accounting being the most dominant factor through recording efficiency. Conversely, digital payment had a significant but negative effect. This was due to the administrative costs of transactions, which reduced profit margins, and liquidity constraints due to the settlement time lag, which hampered daily capital turnover. This study suggests that MSMEs optimize their digital accounting systems and be more careful in managing digital payment service costs.